(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to map research trends on the development of chemistry learning materials oriented toward critical and scientific thinking skills. A bibliometric study was conducted by analyzing scientific publications indexed in multiple reputable databases, namely Scopus, Web of Science, and Google Scholar, over the past five years (2020–2025). The data were analyzed using VOSviewer software to identify keyword trends, author collaborations, geographical distribution, and dominant topics. The results revealed a significant increase in related publications, with a strong emphasis on inquiry-based, problem-based, and scientific approaches. International collaborations are also growing, although they remain concentrated in certain countries. The findings highlight research gaps, particularly the lack of integration between critical and scientific thinking skills within a single learning framework. This study provides a comprehensive overview that can serve as a foundation for researchers and stakeholders in designing future strategies for the development of chemistry education.